S-shaped Curve of Phonological Standardization – Six Surveys in the Tsuruoka and Yamazoe Areas - Inoue, Fumio (Slavia Centralis, 2020)
This paper is concerned with the speed of linguistic change. If social variation is a reflection of linguistic change, the scene of the linguistic change can be caught in action as a palpable phenomenon. However there is one theoretical question, the distinction of "real time" and "apparent time". In order to observe linguistic change repeated surveying is necessary. The tradition of Japanese dialectology provides us with several examples of repetitive surveys. The conclusion of the analysis is as follows. The curve of apparent-time change correspondsto that of real-time change. The total number of years necessary for a linguistic change to be completed is nearly 200 years.
Keywords: real time and apparent time; standardization; S-curve; speed of diffusion